2008
DOI: 10.1128/jb.00566-08
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Neisseria gonorrhoeae NCCP11945

Abstract: Neisseria gonorrhoeae is an obligate human pathogen that is the etiological agent of gonorrhea. We explored variations in the genes of a multidrug-resistant N. gonorrhoeae isolate from a Korean patient in an effort to understand the prevalence, antibiotic resistance, and importance of horizontal gene transfer within this important, naturally competent organism. Here, we report the complete annotated genome sequence of N. gonorrhoeae strain NCCP11945.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
67
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 9 publications
(1 reference statement)
8
67
0
Order By: Relevance
“…4B); this region is flanked by regions of high sequence identity (88.5% to 94.2%). Similar results were obtained in a BLASTn search of the nucleotide database that returned partial alignments among seven meningococcal genomes (strain 8013 [37], ␣14 [41], Z2491 [35], FAM18 [3], 053442 [36], ␣710 [22], and MC58 [46]) and two gonococcal genomes (strains NCCP11945 [8] Analysis of fH binding to strains not expressing fHbp. fH bound to the surface of the meningococcus retains its activity as a cofactor for fI-mediated cleavage of C3b and enhances survival of N. meningitidis in the presence of the human complement system (38).…”
Section: Resultssupporting
confidence: 53%
“…4B); this region is flanked by regions of high sequence identity (88.5% to 94.2%). Similar results were obtained in a BLASTn search of the nucleotide database that returned partial alignments among seven meningococcal genomes (strain 8013 [37], ␣14 [41], Z2491 [35], FAM18 [3], 053442 [36], ␣710 [22], and MC58 [46]) and two gonococcal genomes (strains NCCP11945 [8] Analysis of fH binding to strains not expressing fHbp. fH bound to the surface of the meningococcus retains its activity as a cofactor for fI-mediated cleavage of C3b and enhances survival of N. meningitidis in the presence of the human complement system (38).…”
Section: Resultssupporting
confidence: 53%
“…txf was detected as a sequence inserted into ST1407 contig 061 and is referred to as GR8 in Tables 1 and 2. This inserted sequence deleted 1,106 bp of sequence from the reference NCCP11945 genome (9). Similar to the opa query, this inserted sequence did not map to any region in the NCCP11945 (9) or FA1090 (12) genome.…”
Section: Resultsmentioning
confidence: 93%
“…Using the previously reported NCCP11945 gonococcal genome (9) as a scaffold, we further assembled these 573 contigs into 91 continuous contigs with an average size of 22,500 bp. These 91 larger contigs covered 2,029,064 bp (91.1%) of the NCCP11945 reference genome (9). The vast majority of the gaps between these contigs fell into homopolymeric regions of the N. gonorrhoeae genome.…”
Section: Bacterial Collection (California)mentioning
confidence: 99%
“…Despite a high respiratory capacity that is comparable to that of aerobic bacteria, gonococcal physiology is typical of a microaerophile. It has only a single cytochrome oxidase, cytochrome cbb 3 , which in other bacteria has a very high affinity for oxygen (1)(2)(3)(4)(5). We previously suggested that its high respiratory capacity enables gonococci to minimize oxidative damage from reactive oxygen species generated both from its own respiratory metabolism and by other bacteria that share its environment (6).…”
mentioning
confidence: 99%